Development of Science, Environmental, Technology, and Community Based on E-Module in Science Subject to Improve Learning Outcomes - Marningot H Silalahi; Sahyar Sahyar; Wawan Bunawan (RIRAI Publisher, 2023)
To find E-Modul for Science subject based on SETS to increase the students learning outcome at Class VII Junior High School SMPN 3 Pulau Rakyat. This type of research is oriented towards research and development (R&D) research that produces products. The steps for the development research used are the Addie development model developed by Dick and Carey. Development of E-Modules based on SETS in Science Learning to Improve Learning Outcomes of Class VII Students of SMPN 3 Pulau Rakyat which were developed valid research and entitled to be used as learning tools for science lessons in class VII. It is also in Science Learning to Improve Learning Outcomes of Class VII Students of SMPN 3 Pulau Rakyat which were developed effectively in improving student learning outcomes in class VII students. E-Modules based on SETS in Science Learning to Improve Learning Outcomes of Class VII Students of SMPN 3 Pulau Rakyat which were developed effectively in improving student learning outcomes in class VII students.